Solusi untuk Meningkatkan Kualitas Kerja dan Kesehatan di Desa Kare Kecamatan Kare Kabupaten Madiun melalui Manajemen Kelelahan Berbasis Audiovisual - Prihartini Widiyanti; Fitriyatul Qulub; Akhmad Jayadi; Gadis Meinar Sari (I-Com: Indonesian Community Journal, 2023)
Kare Village is one of the Madiun Regency communities with the potential to become a tourist destination. The goal of community service with an ecotourism theme is to establish a tourist destination where people collaborate effectively, raise public knowledge about health, and provide health facilities that adhere to health protocols. Many advantages will accrue from effective ecotourism management. Kare Village has a lot of tourism potential because it is located on the slopes of Mount Wilis. The Kare Village community's active participation in the Assisted Village Development Program (PPDB) is highlighted through ecotourism. Local people are being trained on the sustainable management of occupational weariness with the assistance of the PPDB community, which will improve the health and living standards of the inhabitants of Kare Village.